Spirituality and Anxiety in Critical Care Patients' Families: A Systematic Review - Ninik Ambar Sari; Merina Widyastuti; Putri Aprilia Rifah (Poltekkes Kemenkes Jakarta III, 2021)
The critical care room is an independent hospital with special staff and special equipment for observation, care and therapy of patients suffering from life-threatening illnesses, injuries or complications. Families in critical rooms usually experience anxiety, fear, and panic. One of the efforts to reduce anxiety is to get closer to God Almighty to increase spirituality. The review aims to obtain information about the spiritual level with anxiety in patients' families in critical care rooms at the hospital. A systematic review was carried out using the PRISMA (Prefered Reporting Items for Systematic Reviews and Meta-analysis) reporting technique with article selection using eligibility criteria. Search journals using Elsevier, PubMed, ScienceDirect, Google Scholar, Springer, and ProQuest databases from June to July 2021. Using English keywords, three journals are obtained; through Indonesian, six journals are obtained. The results of nine journals that have been analyzed by researchers as a whole are 57.5% of good family spiritual and 52.5% moderate family anxiety. This decrease in anxiety was caused by the spiritual services provided to respondents in the form of praying. The spiritual approach can be used as input for nurses to provide interventions to all patients' families in the hospital, especially those who experience anxiety.